PREMENSTRUAL SYNDROME (PMS) PADA MAHASISWI PRODI D-III KEPERAWATAN FAKULTAS ILMU KESEHATAN UNIVERSITAS BAKTI TUNAS HUSADA PREMENSTRUAL SYNDROME (PMS) IN D-III NURSING PROGRAM STUDENTS FACULTY OF HEALTH SCIENCES BAKTI TUNAS HUSADA UNIVERSITY - Sambas, Etty Komariah; Enok, Nurliawati (LPPM Universitas Bakti Tunas Husada, 2024)
Symptoms of premenstrual syndrome (PMS) are psychosomatic symptoms that commonly occur in women of childbearing age starting from adolescence. PMS experienced in the long term can affect the quality of life due to disruption of activities and emotions. The purpose of this study was to identify symptoms of premenstrual syndrome (PMS) including physical, psychological and behavioral changes during PMS in students. This research is a quantitative descriptive study. The participants were 171 students which were selected by a purposive sampling, with the inclusion criteria being PMS and not having reproductive disorders. The results of the study showed that the physical changes during premenstrual syndrome (PMS) that experienced mostly were lower abdominal pain (55.6%), the psychological changes were mood swings (64.9%) and behavior changes was fatigue (39.8%). The conclusion of this study is that the majority of students experienced premenstrual syndrome (PMS). Imbalance of body hormones, especially estrogen and progesterone during menstruation, has been identified as the main cause of premenstrual syndrome (PMS) symptoms. It is suggested that students can increase their knowledge regarding how to reduce and deal with the symptoms of premenstrual syndrome (PMS) appropriately. Keywords : Symptoms, Premenstrual SyndromeABSTRAK Gejala premenstrual syndrome (PMS) adalah gejala psikosomatis yang umum terjadi pada wanita usia subur berawal dari usia remaja. PMS yang dialami dalam jangka panjang dapat mempengaruhi kualitas hidup akibat dari gangguan aktifitas dan emosi yang dialami. Tujuan penelitian ini untuk mengidentifikasi gejala premenstrual syndrome (PMS) meliputi perubahan fisik, psikis dan perilaku semasa PMS pada mahasiswa. Metode penelitian ini menggunakan metode deskriptif kuantitatif. Jumlah responden sebanyak 171 orang yang dipilih melalui purposive sampling, dengan kriteria inklusi mengalami PMS dan tdiak memiliki gangguan reproduksi. Hasil penelitian menunjukkan perubahan fisik semasa premenstrual syndrome (PMS) yang sering dialami ialah nyeri perut bagian bawah (55.6%), perubahan psikis semasa premenstrual syndrome (PMS) yang sering dialami ialah mood menjadi labil (mood swings) (64.9%) dan perubahan perilaku semasa premenstrual syndrome (PMS) yang sering dialami ialah kelelahan (39.8%). Simpulan dari penelitian ini ialah gejala premenstual syndrome (PMS) mayoritas dialami oleh mahasiswi Prodi D-III Keperawatan terutama perubahan psikis. Ketidakseimbangan hormon tubuh terutam aestrogen dan progesterone semasa menstruasi, diidentifikasi merupakan penyebab utama gejala premenstrual syndrome (PMS). Saran diharapkan mahasiswi dapat meningkatkan pengetahuan mengenai cara mengurangi dan mengatasi gejala premenstrual syndrome (PMS) yang dialami dengan tepat. Kata Kunci : Gejala, Premenstrual Syndrome (PMS)